PENGOLAHAN SAMPAH PLASTIK BERBASIS KEARIFAN LOKAL DI RW.03 KELURAHAN BENTIRING PERMAI KECAMATAN MUARA BANGKAHULU KOTA BENGKULU - Febrian Adhaz; Fitriyani Harahap; Ligi Dwi Septiani; Nur’i Putri Harsida; Royki Setiawan; Trissa Irani (UNIB Press, 2025)
Waste management cannot be separated from the diverse and developing lifestyles of society. Therefore, support with technological facilities is needed in terms of waste management. The problem regarding waste is faced by one of the areas in RW.03, Bentiring Permai Village, Muara Bangkahulu District, Kota Bengkulu. Ecobricks and tissue holders were chosen as the solution offered to reuse plastic waste. The advantage of ecobricks is that the manufacturing technique is relatively easy for the community to understand. The research method uses a qualitative research method by observing the conditions directly how the condition of environmental cleanliness is polluted by plastic waste. This research uses a descriptive study approach, namely the problem-solving procedure investigated is carried out by describing the conditions or objects of research. To be able to solve the problem of inorganic waste so that how to overcome the large population of inorganic waste while simultaneously inviting the local community to support the work program to change the inorganic waste into ecobricks. Ecobricks are a simple way to recycle plastic waste